THE INFLUENCE OF TECHNOLOGY, DIGITAL MATERIALS, AND VIRTUAL LEARNING ENVIRONMENTS ON EDUCATIONAL FAIRNESS ACROSS VARIOUS ETHNIC GROUPS (Konferensiyalar | Conferences, 2024)
This paper investigates how various ethnic groups' educational outcomes are affected by technology. Technology can both alleviate and deepen educational gaps among various ethnic communities in today's more digitally connected society. This article provides insight into how technology can be used to advance equity and inclusivity in education by analyzing how it affects learning opportunities, facilitates better access to resources, and shapes educational experiences. To help educators, policymakers, and stakeholders better understand how to use technology to support the academic success of students from diverse ethnic backgrounds, this study will analyze current trends, challenges, and best practices.